Performance Evaluation of Human Powered Air Conditioning System (International Journal of Advanced Research in Science, Management and Technology, 2020)
Human power is the earlier source of power. In present work use of human power is demonstrated to work as a prime mover to Vapour Compression Refrigeration (VCR) system to drive its compressor. A system is designed which is known as Human Powered Air Conditioning System (HPACS) which uses pedal power from bicycle to supply power to compressor with the help of chain drive mechanism. This system may be helpful for the people living in re-mote areas; those are suffering from non-availability of electricity, frequent power cuts for extended period of time. This system may help those peoples by providing cooled air in extreme summer conditions which uses their own efforts, also help them for their physical fitness. Performance of HPACS is evaluated by considering various aspects of air conditioning.
Keywords: Human Power, Pedal Power, VCR (Vapour Compression Refrigeration), HPACS (Human Power Air Conditioning System), COP (Coefficient of Performance), DBT (Dry Bulb Temperature), WBT (Wet Bulb Temperature). RPM (Revolutions Per Minute).